Mechanisms of Antibacterial Activity of MgO: Non‐ROS Mediated Toxicity of MgO Nanoparticles Towards Escherichia coli. Issue 6 (17th December 2013) - Leung, Yu Hang; Ng, Alan M. C.; Xu, Xiaoying; Shen, Zhiyong; Gethings, Lee A.; Wong, Mabel Ting; Chan, Charis M. N.; Guo, Mu Yao; Ng, Yip Hang; Djurišić, Aleksandra B.; Lee, Patrick K. H.; Chan, Wai Kin; et al.
<x xml:space="preserve">Abstract</x> The toxicity of metal oxide nanomaterials and their antimicrobial activity is attracting increasing attention. Among these materials, MgO is particularly interesting as a low cost, environmentally‐friendly material. The toxicity of MgO, similar to other metal oxide nanomaterials, is commonly attributed to the production of reactive oxygen species (ROS). We investigated the toxicity of three different MgO nanoparticle samples, and clearly demonstrated robust toxicity towards Escherichia coli bacterial cells in the absence of ROS production for two MgO nanoparticle samples. Proteomics data also clearly demonstrate the absence of oxidative stress and indicate that the primary mechanism of cell death is related to the cell membrane damage, which does not appear to be due to lipid peroxidation.